The Role of the Manufacturing Industry in the Economy of West Java Province : An Input-Output Analysis Approach - Lukman Lukman; Princess Nurjanah; Awani Ceria Luksita; Hepi Prayudiawan; Suhendra Suhendra (Indonesian Economic Review, 2025)
The West Java government is directing the development of an industrial-based economy. This study analyzes the relationship between the manufacturing industry sector and other economic sectors, identifying the multiplier effect and leading sectors in the manufacturing industry to be developed in West Java. This study is a quantitative descriptive study using the input-output analysis method in 2016. The results of the study indicate that the manufacturing industry sector can encourage the construction sector as its downstream sector and attract the wholesale and agricultural sectors as its upstream sectors. When viewed from the multiplier effect side, the manufacturing industry sector has not been able to become a sector with the highest income multiplier value and workforce multiplier in West Java. The manufacturing industry sub-sectors that are key sectors in the economy of West Java Province are the Textile and Apparel Industry; Metal Goods, Computers, Electronic Goods, Optics and Electrical Equipment Industry; Transportation Equipment Industry; Chemical, Pharmaceutical and Traditional Medicine Industry Sub-sector; Machinery and Equipment Industry (YTDL).